Mathematical modeling of human body for lifting task - Ku Nor Syamimi, Ku Ismail (IEEE Conference Publications, 2014)
Proceeding of The IEEE International Conference on Control System, Computing and Engineering 2012 (ICCSCE 2012) at Penang, Malaysia on 23 November 2012 through 25 November 2012